Composite material containing industrial hemp fibers as well as preparation method and application of composite material

By mixing industrial hemp fibers with thermoplastic polyurethane and crosslinking agent in a twin-screw extruder and preparing through supercritical foaming process, the shortcomings of existing insole materials are solved, and the durability, antibacteriality and lightness are achieved. Efficient antibacterial and wear resistance, suitable for daily necessities such as insoles.

CN119286040APending Publication Date: 2025-01-10ZHEJIANG ALLAN NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411598473.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing insole materials have shortcomings in terms of durability, antibacteriality and lightness, especially the cannabis insoles are prone to wear and have poor shock resilience, while EVA and natural rubber insoles are not breathable and prone to bacterial mold.

Method used

Industrial hemp fiber is used as the main material, and it is heated by soaking it in aqueous pectin enzyme solution, crushing it into powder, and mixing it with thermoplastic polyurethane and crosslinking agent in a twin-screw extruder, through supercritical foaming process Prepare composite materials that are wear-resistant, antibacterial and lightweight.

Benefits of technology

It has achieved excellent antibacterial effect of composite materials, especially inhibiting Staphylococcus and E. coli, with low density and high elasticity, suitable for daily necessities such as insoles, and has a wide range of application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005127600150000061
    Figure BDA0005127600150000061
  • Figure BDA0005127600150000071
    Figure BDA0005127600150000071
Patent Text Reader

Abstract

The invention discloses a composite material of a high-molecular polymer, and particularly discloses a composite material containing industrial hemp fibers, a preparation method and application of the composite material. The composite material containing the industrial hemp fibers has an excellent antibacterial effect, particularly can inhibit staphylococcus and escherichia coli, is low in density, excellent in elasticity and excellent in wear resistance, and can be widely applied to the fields of automobiles, furniture, shoe materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to high molecular polymers, and in particular to a composite material of industrial hemp fibers, a preparation method and application thereof. Background Art

[0002] Shoes are one of the most commonly used daily necessities in life. As people's living standards gradually improve, the quality requirements for shoes are also gradually increasing. In general, people always hope that shoes have better cost-effectiveness and comfort, so durability and lightness become the main evaluation indicators of shoes. Based on this, the insole part of the shoe becomes the most important part affecting the cost-effectiveness and comfort evaluation of the shoe. The main categories of insoles on the current market include hemp insoles, cotton insoles, EVA insoles and natural rubber insoles.

[0003] Due to the limitations of the properties of the raw materials themselves, different types of insoles have different problems. For example, hemp insoles have excellent antibacterial effects, but they are easy to wear and not durable, and have poor shock resistance and resilience. Another example is EVA insoles or natural rubber insoles, although they have good shock resistance and resilience, they are not breathable and easily breed bacteria and mold.

[0004] Therefore, in the face of the above-mentioned deficiencies in the prior art, seeking a wear-resistant, antibacterial and lightweight insole material is still a constant demand in the industry. Summary of the invention

[0005] In view of the defects in the above-mentioned prior art, the purpose of the present invention is to provide a composite material based on industrial hemp fiber, which has the properties of wear resistance, antibacterial and lightness, and has a wide application prospect in daily necessities, especially in the field of insoles.

[0006] The present invention provides a method for preparing a composite material containing industrial hemp fiber, which comprises the following steps:

[0007] (1) Cut the industrial hemp bast into pieces of 0.1-1 cm 2 The small pieces are dried, immersed in a pectinase aqueous solution, rinsed, placed in ethanol, and NaOH and tert-butyl peroxide are added, then heated to boiling, rinsed and dried to obtain crude industrial hemp fiber;

[0008] (2) using a pulverizer or an ultrafine pulverizer to prepare the crude industrial hemp fiber into powder;

[0009] (3) mixing 60-80 parts of thermoplastic polyurethane and 0.2-0.3 parts of a first crosslinking agent in a twin-screw extruder at 120-150° C. to obtain a pre-crosslinked polyurethane, and then mixing the pre-crosslinked polyurethane, 10-30 parts of the industrial hemp fiber powder, 5-20 parts of polyether amide and a second crosslinking agent in a twin-screw extruder at 120-150° C. to obtain a pre-foamed material;

[0010] (4) The pre-foamed material is prepared by a supercritical foaming process to obtain the composite material.

[0011] In one embodiment of the present invention, in step (1), the concentration of the pectinase aqueous solution is 2-3 g / mL, preferably 2.5 g / mL, and the soaking time is 0.5-2 hours, preferably 1 hour.

[0012] In a certain embodiment of the present invention, in step (1), the content of sodium hydroxide is 10-15 g / L, preferably 12 g / L, and the content of tert-butyl peroxide is 25-35 g / L, preferably 30 g / L.

[0013] In one embodiment of the present invention, in step (2), the particle size of the industrial hemp fiber is 100-1000 mesh; preferably 200-400 mesh; and most preferably 400 mesh.

[0014] In a certain embodiment of the present invention, in step (3), the first cross-linking agent is tert-butyl peroxycarbonate-2-ethylhexyl ester; and the second cross-linking agent is di-tert-butyl peroxide isopropylbenzene.

[0015] In one embodiment of the present invention, in step (3), the amounts of the components used are as follows by weight:

[0016] The above industrial hemp fiber powder: 10-30 parts;

[0017] Thermoplastic polyurethane: 60-80 parts;

[0018] Polyether amide: 5-20 parts;

[0019] 2-Ethyl tert-butyl peroxycarbonate: 0.1-0.3 parts;

[0020] Di-tert-butyl peroxide isopropylbenzene: 0.1-0.3 parts.

[0021] In a certain embodiment of the present invention, in step (4), the supercritical foaming process is: at 50-55°C, the pre-foamed material is placed in the cavity of a supercritical foaming device, carbon dioxide is introduced to replace the air in the cavity, carbon dioxide is continued to be introduced to pressurize the cavity to 12-15Mpa, and the pressure is released after full saturation for 0.5-5 hours to obtain the composite material.

[0022] In a certain scheme of the present invention, in step (4): the supercritical foaming process is: at 50°C, the pre-foamed material is placed in the cavity of a supercritical foaming device, carbon dioxide is introduced to replace the air in the cavity, the pre-foamed material is placed in the cavity of a supercritical foaming device, carbon dioxide is introduced to replace the air in the cavity, carbon dioxide is continued to be introduced and pressurized to 12Mpa, and the pressure is released after full saturation for 2.5 hours to obtain the composite material.

[0023] The present invention also provides a composite material containing industrial hemp fibers, and the composite material containing industrial hemp fibers is prepared by the above-mentioned preparation method.

[0024] The present invention also provides an application of the composite material containing industrial hemp fiber in automobiles, furniture and shoe materials, preferably in shoe materials.

[0025] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0026] The reagents and raw materials used in the present invention are commercially available.

[0027] The positive and progressive effects of the present invention are:

[0028] (1) The composite material containing industrial hemp fiber of the present invention has excellent antibacterial effect, especially capable of inhibiting Staphylococcus aureus and Escherichia coli.

[0029] (2) The composite material containing industrial hemp fiber of the present invention has low density, excellent elasticity and excellent wear resistance, and the raw materials are easily available, suitable for large-scale production, and has broad application prospects in daily necessities, such as in the fields of automobiles, furniture, and shoe materials, and can be particularly applied to shoe sole materials. DETAILED DESCRIPTION

[0030] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0031] Example 1

[0032] Composite materials containing industrial hemp fibers1

[0033] Step 1: Prepare the Crude Hemp

[0034] Cut 200g of industrial hemp bast into pieces of about 0.5cm 2The small pieces are dried, then soaked in 1L pectinase solution (2.5g / ml) for about 1h, then rinsed with water for 5-6 minutes, and then alkali treated: the small pieces of industrial hemp bast after the above treatment are placed in 1L ethanol, 30g tert-butyl peroxide, 12g NaOH are added, heated to 78°C, and maintained for 6 hours. Then the small pieces of industrial hemp bast after alkali treatment are washed with water for 5-6 minutes and dried to obtain crude industrial hemp fiber.

[0035] Step 2: Prepare industrial hemp fiber powder

[0036] The crude industrial hemp fiber obtained in step 1 is made into 400 mesh industrial hemp fiber fine powder by a pulverizer.

[0037] Step 3: Prepare the pre-foamed material

[0038] According to the mass parts: 70 parts of thermoplastic polyurethane (Elastollan) and 0.2 parts of the first cross-linking agent (tert-butyl peroxycarbonate-2-ethylhexyl ester) are mixed in a twin-screw extruder at a mixing temperature of 130°C, and then 20 parts of the industrial hemp fiber powder obtained in step 2, 10 parts of polyetheramide (Pebax) and 0.2 parts of the second cross-linking agent (di-tert-butyl peroxide isopropylbenzene) are mixed in a twin-screw extruder at a mixing temperature of 140°C to obtain a pre-foamed material.

[0039] Step 4: Supercritical CO2 Foaming

[0040] The pre-foamed material is cut into strips, and the strips are added into the cavity of a supercritical foaming device at 50° C. After replacing the air in the cavity with carbon dioxide, carbon dioxide is continuously introduced and pressurized to 12 MPa. After being fully saturated for 2.5 hours, the pressure is released to obtain the composite material.

[0041] Example 2

[0042] Composite materials containing industrial hemp fibers2

[0043] According to the preparation method of Example 1, the difference between Example 2 and Example 1 is that in step 2, specifically, the crude industrial hemp fiber obtained in step 1 is made into 200-mesh industrial hemp fiber fine powder by a pulverizer.

[0044] Example 3

[0045] Composite materials containing industrial hemp fibers3

[0046] According to the preparation method of Example 1, the difference between Example 3 and Example 1 is only in step 2. Specifically, the crude industrial hemp fiber obtained in step 1 is made into 1000-mesh industrial hemp fiber fine powder by a pulverizer.

[0047] Example 4

[0048] Composite materials containing industrial hemp fibers4

[0049] According to the preparation method of Example 1, the difference between Example 4 and Example 1 is only in step 2. Specifically, the crude industrial hemp fiber obtained in step 1 is made into 50-mesh industrial hemp fiber fine powder by a pulverizer.

[0050] Example 5

[0051] Composite materials containing industrial hemp fibers5

[0052] According to the preparation method of Example 1, the difference between Example 5 and Example 1 is only that in step 3, specifically, the weight portion of industrial hemp fine powder is 30 parts.

[0053] Example 6

[0054] Composite materials containing industrial hemp fibers6

[0055] According to the preparation method of Example 1, the difference between Example 6 and Example 1 is only that in step 3, specifically, the weight portion of industrial hemp fine powder is 10 parts.

[0056] Example 7

[0057] Composite materials containing industrial hemp fibers7

[0058] According to the preparation method of Example 1, the difference between Example 7 and Example 1 is only that in step 3, specifically, the weight portion of industrial hemp fine powder is 5 parts.

[0059] Example 8

[0060] Composite materials containing industrial hemp fibers8

[0061] According to the preparation method of Example 1, the difference between Example 8 and Example 1 is only the alkali treatment in step (1). Specifically, the alkali treatment is as follows: the small piece of industrial hemp bast after the above treatment is placed in 1L of water, 80mL of hydrogen peroxide and 12g of NaOH are added, and heated to 100°C for 6 hours.

[0062] Example 9

[0063] Composite materials 9

[0064] 70 parts of thermoplastic polyurethane (Elastollan) and 0.2 parts of a first crosslinking agent (tert-butyl peroxycarbonate-2-ethylhexyl) are mixed in a twin-screw extruder at a mixing temperature of 130 degrees Celsius, and then 10 parts of polyetheramide (Pebax) and 0.2 parts of a second crosslinking agent (di-tert-butyl peroxide isopropylbenzene) are mixed in a twin-screw extruder at a mixing temperature of 140 degrees Celsius to obtain a pre-foamed material; the pre-foamed material is cut into strips, and the strips are added into a cavity of a supercritical foaming device at 50°C, and after replacing the air in the cavity with carbon dioxide, carbon dioxide is continuously introduced and pressurized to 12MPa, and the pressure is released after being fully saturated for 2.5 hours to obtain the composite material.

[0065] Effect Example

[0066] The composite material prepared in the above example was evaluated by the following indexes, and the specific method is as follows:

[0067] Density: Tested according to the method specified in GB / T 6343-2009.

[0068] Rebound (%): Tested according to the method specified in reference standard GB / T 10652-2001.

[0069] Wear resistance test: The test is carried out according to the method specified in the reference standard GB / T 1689-1998. The material to be tested is made into a sample strip, glued to a rubber roller, and then tested on an Akron abrasion testing machine. The pre-grinding is 500 turns and its mass is m0 (g). After the sample travels 1.61 km (grinding 3416 turns), its mass is m1 (g). The wear volume of the material is V = (m0-m1) / ρ, where V is the Akron wear volume and ρ is the density of the wear-resistant rubber foam material (g / cm3). The wear volume before and after aging is tested respectively. The aging condition is to place it in an aging box at 100°C for 48 hours.

[0070] Antibacterial performance: Tested according to the method specified in the standard "GB / T 31402-2015 Test method for antibacterial performance of plastic surface". Antibacterial tests were conducted on Staphylococcus aureus and Escherichia coli.

[0071] By the above method: the test results of the embodiment are shown in the following table:

[0072]

[0073]

[0074] The above test results show that the composite material containing industrial hemp fiber of the present invention has excellent antibacterial effect, especially can inhibit Staphylococcus and Escherichia coli. In addition, the composite material containing industrial hemp fiber of the present invention has low density, excellent elasticity and excellent wear resistance, the raw materials are easy to obtain, suitable for large-scale production, and has a wide range of application prospects in daily necessities, especially can be applied to sole materials.

Claims

1. A method for preparing a composite material containing industrial hemp fiber, characterized in that: It includes the following steps: (1) Cut the industrial hemp bast into pieces of 0.1-1 cm 2 The small pieces are dried, immersed in a pectinase aqueous solution, rinsed, placed in ethanol, and NaOH and tert-butyl peroxide are added, then heated to boiling, rinsed and dried to obtain crude industrial hemp fiber; (2) using a pulverizer to prepare the crude industrial hemp fiber into powder; (3) mixing 60-80 parts of thermoplastic polyurethane and 0.2-0.3 parts of a first crosslinking agent in a twin-screw extruder at 120-150° C. to obtain a pre-crosslinked polyurethane, and then mixing the pre-crosslinked polyurethane, 10-30 parts of the industrial hemp fiber powder, 5-20 parts of polyether amide and a second crosslinking agent in a twin-screw extruder at 120-150° C. to obtain a pre-foamed material; (4) The pre-foamed material is prepared through a supercritical foaming process to obtain the composite material containing industrial hemp fiber.

2. The method for preparing a composite material containing industrial hemp fiber as claimed in claim 1, characterized in that: It meets one or more of the following conditions: (1) In step (1), the concentration of the pectinase aqueous solution is 2-3 g / mL, and the soaking time is 0.5-2 hours; (2) In step (1), the content of sodium hydroxide is 10-15 g / L; (3) In step (2), the particle size of the industrial hemp fiber is 100-1000 mesh.

3. The method for preparing a composite material containing industrial hemp fiber as claimed in claim 2, characterized in that: It meets one or more of the following conditions: (1) In step (1), the concentration of the pectinase aqueous solution is 2.5 g / mL, and the soaking time is 1 h; (2) In step (1), the content of sodium hydroxide is 12 g / L, and the content of tert-butyl peroxide is 30 g / L; (3) In step (2), the particle size of the industrial hemp fiber is 200-400 mesh.

4. The method for preparing a composite material containing industrial hemp fiber as claimed in claim 3, characterized in that: In step (2), the particle size of the industrial hemp fiber is 400 meshes.

5. The method for preparing a composite material containing industrial hemp fiber as claimed in claim 1, characterized in that: In step (3), the first cross-linking agent is tert-butyl peroxycarbonate-2-ethylhexyl ester; and the second cross-linking agent is di-tert-butyl peroxide isopropylbenzene.

6. The method for preparing a composite material containing industrial hemp fiber as claimed in claim 1, characterized in that: In step (3), the amounts of the components used are as follows by weight: The above industrial hemp fiber powder: 10-30 parts; Thermoplastic polyurethane: 60-80 parts; Polyether amide: 5-20 parts; 2-Ethyl tert-butyl peroxycarbonate: 0.1-0.3 parts; Di-tert-butyl peroxide isopropylbenzene: 0.1-0.3 parts.

7. The method for preparing a composite material containing industrial hemp fiber as claimed in claim 1, characterized in that: In step (4), the supercritical foaming process is as follows: at 50-55° C., the pre-foamed material is placed in the cavity of a supercritical foaming device, carbon dioxide is introduced to replace the air in the cavity, carbon dioxide is continued to be introduced to pressurize the cavity to 12-15 MPa, and the pressure is released after full saturation for 0.5-5 hours to obtain the composite material.

8. The method for preparing a composite material containing industrial hemp fiber as claimed in claim 7, characterized in that: In step (4): the supercritical foaming process is: at 50°C, the pre-foamed material is placed in the cavity of a supercritical foaming device, carbon dioxide is introduced to replace the air in the cavity, the pre-foamed material is placed in the cavity of a supercritical foaming device, carbon dioxide is introduced to replace the air in the cavity, carbon dioxide is continued to be introduced and pressurized to 12Mpa, and the pressure is released after full saturation for 2.5 hours to obtain the composite material.

9. A composite material, characterized in that: The composite material is prepared by the preparation method as described in any one of claims 1 to 8 above.

10. Use of the composite material containing industrial hemp fiber as claimed in claim 9 in automobiles, furniture and shoe materials, preferably in shoe materials.